2014
DOI: 10.1038/cgt.2014.16
|View full text |Cite
|
Sign up to set email alerts
|

The PPARγ agonist Troglitazone induces autophagy, apoptosis and necroptosis in bladder cancer cells

Abstract: Bladder cancer is a major public health problem worldwide, with relatively high morbidity. However, there are few studies on drug development for bladder cancer. Troglitazone (TZ) is a synthetic ligand of peroxisome proliferator-activated receptor-γ, and it can induce apoptosis and autophagy in a variety of cancer cells. Several studies have indicated that TZ affects both cell growth and differentiation progress and has an inhibitory effect on urinary cancer cells. However, this drug's effect on bladder cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 38 publications
2
44
0
Order By: Relevance
“…However, the role of PPARγ-mediated transcriptional regulation of autophagy remains controversial. Indeed, Troglitazone, a PPARγ agonist, induces autophagy and cell death in bladder cancer cells (Yan et al, 2014), whereas another PPAR agonist, 15d-prostaglandin J 2 , suppresses autophagy in ischemic brain (Xu et al, 2013;Qin et al, 2015).…”
Section: Jun -Activated By Diverse Stressesmentioning
confidence: 99%
“…However, the role of PPARγ-mediated transcriptional regulation of autophagy remains controversial. Indeed, Troglitazone, a PPARγ agonist, induces autophagy and cell death in bladder cancer cells (Yan et al, 2014), whereas another PPAR agonist, 15d-prostaglandin J 2 , suppresses autophagy in ischemic brain (Xu et al, 2013;Qin et al, 2015).…”
Section: Jun -Activated By Diverse Stressesmentioning
confidence: 99%
“…A previous study indicated that the PPARγ agonist troglitazone induces autophagy, apoptosis and necroptosis in bladder cancer cells [27]. However, rosiglitazone, a selective PPAR-γ-inhibitor, is reported to induce autophagy in H295R cells and cell cycle deregulation in SW13 adrenocortical cancer cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…PPAR gamma is also present in other tissues, such as breast [70,71], colon [72][73][74], lung [75,76], ovary [77,78], prostate [79,80] and thyroid [81,82] wherein it mediates several specific functions, such as early development [83], cell proliferation [84], differentiation [85], apoptosis [86], and metabolic homeostasis [87]. Many investigators [88][89][90][91][92][93][94][95][96][97] reported that PPAR gamma was also involved in the control of transcriptional regulation of autophagy. The target genes of PPAR gamma has been reported including ATG7, ATG12, LC3, P62, ULK1, LAMP1, BCL2, Beclin1, Pink1, and Bnip3 [88][89][90][91][92][93][94][95][96][97] (Table 1).…”
Section: Newly Participant Of Autophagy Regulation: Pparsmentioning
confidence: 99%